Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.tree.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

When less is more: positive population-level effects of mortality

Abstract: Experimental and theoretical studies show that mortality imposed on a population can counter-intuitively increase the density of a specific life-history stage or total population density. Understanding positive population-level effects of mortality is advancing, illuminating implications for population, community, and applied ecology. Reconciling theory and data, we found that the mathematical models used to study mortality effects vary in the effects predicted and mechanisms proposed. Experiments predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 54 publications
6
94
1
Order By: Relevance
“…While this is an obvious simplification of the biological reality of complex life cycles, previous studies have shown that such a simple model already catches some essential characteristics of size-structured populations (Schröder et al 2014). In addition, the twostage model is a relatively small deviation from unstructured population models and therefore a suitable tool for comparisons with unstructured models and tests of established ecological theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this is an obvious simplification of the biological reality of complex life cycles, previous studies have shown that such a simple model already catches some essential characteristics of size-structured populations (Schröder et al 2014). In addition, the twostage model is a relatively small deviation from unstructured population models and therefore a suitable tool for comparisons with unstructured models and tests of established ecological theory.…”
Section: Discussionmentioning
confidence: 99%
“…These changes have profound consequences for energy acquisition and energy use in individuals (Peters 1983;Kooijman 2000;Persson and de Roos 2013). Including differences in body size over ontogeny and basic principles of animal metabolism (i.e., somatic growth is a food-dependent process and maintenance of the body requires energy) in population models, has been shown to strongly affect population and consumer-resource dynamics (Schröder et al 2009;Persson and de Roos 2013;Schröder et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For populations where negative density-dependent processes (e.g., cannibalism, competition) increase with abundance, an increase in mortality can result in an increase in a population's recruitment rate (Abrams 2009, Zipkin et al 2009, Schröder et al 2014. This increase in the number of individuals recruiting into a population, also known as compensation, can result from natural increases in mortality (e.g., disease, predation) or through anthropogenic harvest (Boyce et al 1999, Ohlberger et al 2011).…”
Section: Chapter 3: Outcomes Of Aquatic Invasive Species Management Ementioning
confidence: 99%
“…In contrast, efforts to remove nuisance species can be derailed when compensatory recruitment matches or exceeds harvest rates (Zipkin et al 2008(Zipkin et al , 2009). While rarer, compensatory recruitment can result in the population exceeding its pre-removal abundance in a phenomenon called overcompensation (Abrams 2009, Zipkin et al 2009, Schröder et al 2014. Given the potential for compensation to adversely affect removal efforts, improving our understanding of the circumstances under which compensation could occur would be of great benefit to managers.…”
Section: Chapter 3: Outcomes Of Aquatic Invasive Species Management Ementioning
confidence: 99%
See 1 more Smart Citation